2016
DOI: 10.1002/mrm.26509
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of magnetic resonance fingerprinting T1 and T2 estimates assessed using the ISMRM/NIST MRI system phantom

Abstract: Purpose The purpose of this study was to evaluate accuracy and repeatability of T1 and T2 estimates of a Magnetic Resonance Fingerprinting (MRF) method using the ISMRM/NIST MRI system phantom. Methods The ISMRM/NIST MRI system phantom contains multiple compartments with standardized T1, T2 and proton density values. Conventional inversion-recovery spin echo and spin echo methods were used to characterize the T1 and T2 values in the phantom. The phantom was scanned using the MRF-FISP method over 34 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
193
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 137 publications
(219 citation statements)
references
References 29 publications
23
193
3
Order By: Relevance
“…Recent studies have looked into improving on the MRF acquisition parameters to make them more robust, improving the reconstruction algorithms and acquiring newer quantitative parameters from this technique 2628 . Given its multiparametric capabilities and repeatability, this technique holds the capability to become a useful MR imaging biomarker 29, 30 . Although the clinical applications and utility of this technique have not been assessed so far, the in-vivo quantitation data in healthy volunteers and in patients are emerging 3133 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have looked into improving on the MRF acquisition parameters to make them more robust, improving the reconstruction algorithms and acquiring newer quantitative parameters from this technique 2628 . Given its multiparametric capabilities and repeatability, this technique holds the capability to become a useful MR imaging biomarker 29, 30 . Although the clinical applications and utility of this technique have not been assessed so far, the in-vivo quantitation data in healthy volunteers and in patients are emerging 3133 .…”
Section: Discussionmentioning
confidence: 99%
“…When combined with diffusion, the MRF T 1 and T 2 values can differentiate prostate cancer from normal tissue and separate low‐grade from high/intermediate‐grade tumors . Because of the flexibility of the sequence design and signal modeling, confounding factors, such as slice profile imperfection, B0, and B1 inhomogeneities can be incorporated into the signal model, which has been shown to improve the accuracy and robustness of MRF scans and provide results with high repeatability . In a very recent study, 2D MRF was shown to improve detection of hippocampal sclerosis by multiparametric mapping of T 1 and T 2 values .…”
mentioning
confidence: 99%
“…Various sequences can be tailored to this MRF framework depending on the specific tissue properties that need to be measured, including T1, T2, M 0 , perfusion parameters, B 0 , B 1 , etc. Current MRF sequences have been shown to be repeatable[2,13,14]. MRF offers the possibility of bringing quantitative imaging into clinical routine, potentially allowing more precise and automated diagnosis and easier comparison between data acquired in different scans, at different times and in different locations.…”
Section: Resultsmentioning
confidence: 99%
“…Thus high quality individual time point images are explicitly not sought. Despite the significant undersampling, the signal evolution obtained from all the undersampled data can still be matched to the best corresponding MRF dictionary entry and the resulting quantitative maps have been shown to be highly accurate[2] and repeatable (Coefficient of variation of less than 5% for T1 and T2 values)[13]. It is therefore possible to “see through” image artifacts arising from the undersampling during the dictionary-matching step, as the errors are not coherent spatially or temporally [2].…”
Section: Data Acquisitionmentioning
confidence: 99%